Magnetoresistance, temporal evolution, and relaxation of the electrical resistivity in the re-entrant semiconducting La0.80Ba0.20CoO3 perovskite - Sanchez, Rodolfo Daniel (2011)
We report here a study on the electrical and magnetic properties of La1-xBaxCoO3 in the re-entrant semiconducting region (x = 0.20). We find that in this material: (i) the insulator-metal-insulator sequence is unstable and evolves toward a purely semiconducting behavior; the initial ρ versus T curve can be reinstated upon appropriate annealing treatments; (ii) there are relaxation effects that can be seen by changing the polarity of the electrodes; (iii) there is a negative magnetoresistance Δρ/ρ approx. 2-3%, for a field as low as 9 kOe, especially at the metal-insulating transition temperatures; and (iv) there are important fluctuations in the electrical resistivity. Taking into account these experimental observations, we can interpret this material as an inhomogeneous system where two thermodynamic phases, one semiconducting and the other metallic and ferromagnetic, coexist, although they are crystallographically indistinguishable.